PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO, DAN BIAYA OPERASIONAL PADA PENDAPATAN OPERASIONAL TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Kristin Widiasanti; Jeni Susyanti; M Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This study aims to analyze the effect of CAR, NPF, FDR, and BOPO on the profitability of Islamic Commercial Banks in Indonesia. This type of research is quantitative which focuses on the management of numerical data. The populations in the study used all Islamic banks registered in the Financial Services Authority in 2014-2016 as many as 13 banks that met the criteria of 10 banks. Data collection methods using documentation and literature study. The sampling technique used in this study was purposive sampling technique by considering the completenes of quarterly data from the research variables presented on the official website of the Financial Services Authority. Independent variables are CAR, NPF, FDR, and BOPO. While the dependent variable is profitability which is proxied by ROA.Based on the results of the analysis carried out, the results obtained included: 1) CAR has a significant effect on ROA. 2) NPF has no significant effect on ROA. 3) FDR has no significant effect on ROA. 4) BOPO has a significant effect on ROA.Keywords: CAR, NPF, FDR, BOPO, ROA and Syariah Commercial Banks.